Direito ao trabalho: Consideraç\~oes gerais e preliminares - André Gambier Campos (Instituto de Pesquisa Econômica Aplicada (IPEA), 2011)
– The idea of work as a right has been in public debate since the beginning of the contemporary era - and so, intertwined with the discussion of human rights. Over time, the right to work has transmuted in the right to decent work, with all the characteristics ascribed to the latter. In Brazil, the right to work is enshrined in the Constitution of 1988. However, the emphasis of the Constitution is almost only in the wage employment. Therefore, the debate about the right to work has been restricted. Relevant groups of the population which are not engaged in wage employment sit on the sidelines of this debate. Groups such as self-employed workers, cooperative members, household workers and the unemployed. Moreover, the situation of the latter is defining of the right to work, which is realized through the elimination of unemployment. Whatever its nature, unemployment has no place in a society that assumes the right to work.
Keywords: I38; J08; J83; 330; Recht auf Arbeit; Arbeitsmarktpolitik; Brasilien